CONVERSION OF (±)-CITRONELLAL AND ITS DERIVATIVES TO (-)-MENTHOL USING BIFUNCTIONAL NICKEL ZEOLITE CATALYSTS - Indri Badria Adilina; Ralentri Pertiwi; Anny Sulaswatty (Biopropal Industri, 2015)
(±)-Citronellal and its derivatives were converted to (-)-menthol by a one-pot reaction system using zeolite based nickel catalysts. The catalysts were prepared by immobilization of nickel on natural zeolite (NZ) or synthetic zeolite (ZSM-5) by a simple cation exchange method. Calcination and hydrogen treatment procedures were able to significantly increase the surface area and pore volume of NZ based catalysts whereas negligible changes in the properties were observed for that of ZSM-5. Catalytic reactions were carried out at 70ºC by stirring the mixture in the air for cyclization of (±)-citronellal to (±)-isopulegol followed by hydrogenation towards the desired (-)-menthol at 2 Mpa of H2 pressure. The Ni/NZ catalyst was able to convert a (±)-citronellal derivative yielding 9% (-)-menthol (36% selectivity) with conversion up to 24%, whereas Ni/ZSM5 catalyst directly converted 65% (±)-citronellal to give 4% menthol (6% selectivity). These zeolite based catalysts are therefore potential materials for the conversion of biomass feed stock to value-added chemicals.